Estimasi Model Substitusi Tidak Sempurna Volume Perdagangan Indonesia - Dwika Darinda; Aprilianto Amir (Business Perspective Journal, 2022)
The international trade consists of two components, volume and price. The price component is a deflator for international trade. Meanwhile, the volume component can be regarded as the real condition of international trade. In this paper, the author tries to explain the relationship between export and import volumes according to the theoretical basis. The response variable is the quantity (volume) of imports and exports. Meanwhile, the control variables, such as GDP and REER, are in accordance with the "imperfect substitute" model. Based on multiple regression analysis, it is known that the volume of imports is influenced by purchasing power and the negative effect of the relative price of imported goods on domestic prices. Meanwhile, export volume growth was positive by production capacity and negative effect by international relative on domestic costs. Keywords: trade, imperfect substitutes, ECM, volume component